2012
DOI: 10.1111/fwb.12046
|View full text |Cite
|
Sign up to set email alerts
|

Alternative tactics in spawning site selection by brook trout (Salvelinus fontinalis) related to incubation microhabitats in a harsh winter environment

Abstract: Summary 1. Species with distributions that span a broad range of latitudes may have populations that exhibit distinct life history traits associated with environmental gradients. The majority of previous studies have indicated a strong association between spawning site selection by brook trout (Salvelinus fontinalis) and the presence of upwelling groundwater, but does this generalisation extend to the thermal regimes experienced at northern sites? 2. We investigated the role of hyporheic flow in redd site sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 61 publications
1
6
0
Order By: Relevance
“…Although the sample size was small, the majority of natural redds were located on convex or transitional bedforms, where downwelling was prevalent (Bowerman 2013). Other researchers have also observed that bull trout and closely related brook trout (Salvelinus fontinalis) often select spawning microhabitats with localized downwelling (Baxter and Hauer 2000;Franssen et al 2013). In this study, the greatest downwelling rates occurred at spawning sites located above steep riffles and logjams, each of which created a defined vertical step in the streambed.…”
Section: Redd Creation and Spawning Site Characteristicssupporting
confidence: 49%
See 2 more Smart Citations
“…Although the sample size was small, the majority of natural redds were located on convex or transitional bedforms, where downwelling was prevalent (Bowerman 2013). Other researchers have also observed that bull trout and closely related brook trout (Salvelinus fontinalis) often select spawning microhabitats with localized downwelling (Baxter and Hauer 2000;Franssen et al 2013). In this study, the greatest downwelling rates occurred at spawning sites located above steep riffles and logjams, each of which created a defined vertical step in the streambed.…”
Section: Redd Creation and Spawning Site Characteristicssupporting
confidence: 49%
“…3). Within each redd where data were available, the difference between intragravel and surface water temperature was calculated as ⌬T = |intragravel temperaturestream temperature| (Franssen et al 2013). Groundwater inputs into shallow streambed sediments can be identified by high ⌬T (e.g., ⌬T > 2) and stable hyporheic temperatures similar to average groundwater temperatures in the Metolius basin (7 to 9°C; Gannett et al 2003).…”
Section: Water Quality Hydraulic and Sedimentary Characteristics Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…Surface water infiltration into the streambed is driven by gradients in bed topography and water surface elevation, which are greatest near riffle crests (Marzadri et al, 2010;Tonina & Buffington, 2007). While hyporheic fluxes often are proposed as important cues for salmon redd site selection, previous studies have reported mixed results, with some finding that redds were located in areas of high hyporheic flows (Baxter & Hauer, 2000;Bean et al, 2015;Geist & Dauble, 1998), while others did not (Benjankar et al, 2016;Curry & Noakes, 1995;Franssen et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Alternately, phenotypic divergence may arise from differences in developmental patterns associated with rearing habitat. In this region, most stream-dwelling brook trout spawn in riffle-crest habitats associated with up-or downwelling flows (Franssen et al 2013), making reproduction isolation an unlikely driver of phenotypic variation. Without interspecific competition and (or) predation (at least from other fish), fish in this system would fill available areas in an assortative manner based on hierarchy and home territories.…”
Section: Discussionmentioning
confidence: 99%